Using Chronopotentiometry to Better Characterize the Charge Injection Mechanisms of Platinum Electrodes Used in Bionic Devices - Harris, Alexander R.; Newbold, Carrie; Carter, Paul; Cowan, Robert; Wallace, Gordon G. (Frontiers in Neuroscience, 2019)
The safe charge injection capacity and charge density of neural stimulating electrodes is based on empirical evidence obtained from stimulating feline cortices. Stimulation induced tissue damage may be caused by electrochemical or biological mechanisms. Separating these mechanisms requires greater understanding of charge transfer at the electrode-tissue interface. Clinical devices typically use a biphasic waveform with controlled current. Therefore, the charge injection mechanism and charge injection capacity of platinum was assessed on a commercial potentiostat by chronopotentiometry (controlled current stimulation). Platinum is a non-ideal electrode, charge injection by chronopotentiometry can be passed via capacitive and Faradaic mechanisms. Electrodes were tested under a variety of conditions to assess the impact on charge injection capacity. The change in electrode potential (charge injection capacity) was affected by applied charge density, pulse length, pulse polarity, electrode size, polishing method, electrolyte composition, and oxygen concentration. The safe charge injection capacity and charge density could be increased by changing the electrode-solution composition and stimulation parameters. However, certain conditions (e.g., acid polished electrodes) allowed the electrode to exceed the water electrolysis potential despite the stimulation protocol being deemed safe according to the Shannon plot. Multiple current pulses led to a shift or ratcheting in electrode potential due to changes in the electrode-solution composition. An accurate measure of safe charge injection capacity and charge density of an implantable electrode can only be obtained from suitable conditions (an appropriately degassed electrolyte and clinically relevant electrode structure). Cyclic voltammetric measurement of charge storage capacity can be performed on implantable electrodes, but will not provide information on electrode stability to multiple chronopotentiometric pulses. In contrast, chronopotentiometry will provide details on electrode stability, but the minimum time resolution of typical commercial potentiostats (ms range) is greater than used in a clinical stimulator (μs range) so that extrapolation to short stimulation pulses is required. Finally, an impedance test is typically used to assess clinical electrode performance. The impedance test is also based on a biphasic chronopotentiometic waveform where the measured potential is used to calculate an impedance value. Here it is shown that the measured potential is a function of many parameters (solution composition, electrode area, and surface composition). Subsequently, impedance test results allow electrode comparison and to indicate electrode failure, but use of Ohm’s law to calculate an impedance value is not valid.